A spectroscopic ellipsometry study on the variation of the optical constants of tin-doped indium oxide thin films during crystallization - Jung, YS (PERGAMON-ELSEVIER SCIENCE LTD, 2004)
In this paper. the variation of the optical constants of tin-doped indium oxide thin films during thermal treatment was explored using spectroscopic ellipsometry based on appropriate analysis models combining a Drude absorption edge and Lorentz oscillators. It was found that the refractive indices and the extinction coefficients show different behaviors depending on depth, thermal treatment time and temperature. The optical constants varied more abruptly in the lower part of the films, which confirms the model that crystallization starts from the film-substrate interface. Hall measurement showed that the significant increase in the extinction coefficients in the near infrared range is due to the increased number of free electrons. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: TEMPERATURE; DEPOSITION; NITROGEN; LAYERS